Assessment of economic impacts of differentiated carbon reduction targets: a case study in Tianjin of China - Yu Qi; Hancheng Dai*; Yong Geng*; Yang Xie (Journal of Cleaner Production, 2018)
The Computable General Equilibrium (CGE) model could capture the full range of interaction and feedback effects among different agents in the economic system. This study analyzes the economic impacts of differentiated carbon reduction targets by using a two-region CGE model in Tianjin Municipal City of China (hereafter “Tianjin”). Firstly, based on a business-as-usual (BaU) scenario and seven proposed carbon reduction scenarios, this paper quantifies the macroeconomic impacts of different carbon reduction targets in both regions, especially the carbon reduction costs and industrial output. Furthermore, several typical industries in Tianjin are chosen to explore how their competitiveness is affected under different carbon allocation scenarios. The results show that compared with the BaU scenario, the Gross Domestic Product (GDP) in Tianjin would achieve the highest growth rate if the carbon intensity reduction target is set at 65% in Tianjin whereas 55% in the rest of China (ROC). Meanwhile, residents’ welfare loss in Tianjin will be the largest if carbon intensity reduction target in 2030 is set to be 65% in Tianjin and 75% in ROC. Also, the local pillar industries (including electronic sector and the metal smelting sector) would benefit from the carbon reduction policy, while the paper sector would be negatively influenced. Policy recommendations are raised, in which several factors should be fully considered, including development stages, resource endowments, technical levels and local environmental carrying capacity.